Isolasi Kurkumin dari Kunyit Putih dengan Menggunakan Metode Maserasi dan Kromatografi Lapis Tipis (KLT) - Henni Cintya; Michelle Angie Chan; Anggreni Purba; Tanezsia Kokita; Farrencia Destinyie; Wilbert Bernardi (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Curcumin is an active compound of the polyphenol group found in turmeric. Isolation and identification of curcumin have been done in plants which belong to genus Curcuma, such as Curcuma zedoaria. Curcumin is known for its antitumor, antioxidant properties and has many health benefits. Curcumin have many therapeutic activities, such as antioxidant, anti-inflammatory, and anticarcinogenic. The isolation and identification process was used maceration and TLC (Thin Layer Cromatography) method. The reason using this methods are efficient, easy, simple, and cheap. The extract characterization gave the water content valued at 0,37%, total ash valued at 0,7%, the acid insoluble ash valued at 0,291%. All of these extract characterization adequate the provision. From the results of TLC with a mixture of mobile phase (eluent) i.e. chloroform:ethanol:acetic acid with a ratio of 94:5:1, it shows that there are 3 stains with Rf values, respectively, for curcumin standard Rf1 0.1-0.125; Rf2 0.1375-0.1875; Rf3 0.3375-0.375. As for the white turmeric extract obtained Rf1 0.125-0.225; Rf2 0.1875-0.475; Rf3 0.425-0.675. Meanwhile, the mobile phase mixture (eluent) of chloroform:n-hexane:methanol with a ratio of 1:1:0,1 showed that there were 3 stains with Rf values, respectively, for curcumin the standard was Rf1 0.1-0.125; Rf2 0.1375-0.1875; Rf3 0.3375-0.375. As for the white turmeric extract obtained Rf1 0.1-0.125; Rf2 0.125-0.225; Rf3 0.35-0.375.